Enhancing productivity for poverty reduction in India. - Gupta, Kanupriya (ADB Briefs, 2020)
This brief presents findings from a study on labor productivity across various sectors in India and its impact on poverty reduction.Data gathered from the study show that agriculture, construction, and unregistered manufacturing employ the bulk of Indias workforce. The brief posits that higher productivity levels in these and other sectors is needed to accelerate the rate of poverty reduction in the country. Policy recommendations outlined in the brief call for significant improvements in the agriculture sector that accounts for majority of the workforce as well as sustainable investments on education, training, and skills development to meet employment demands in other sectors.